FINDING A LIVING GOD: Learn from Stanley J. Samartha - Firman Panjaitan (MAHABBAH: Journal of Religion and Education, 2022)
The religious concept of God has essentially "killed" the real existence of God. The understanding of God has been narrowed through religious dogmas so that God no longer lives universally but is limited to religious dogmas that try to live it in its own religious way. Departing from this problem, this article aims to discuss efforts to find God who lives in the existence of human life. By using literature studies, especially examining Samartha's views on the power of syncretism to build an attitude of pluralism, the findings are that syncretism is a means to animate universal values in religion. Syncretism is the power to foster synergy between culture and religion, so as to form a grounded contextual understanding of the rules of the good life. Likewise with God. Through contextualization based on syncretism, God who has been killed by religious dogmas is brought back to life, so that it can greet life in accordance with the context in which God lives. God is seen universally and at the same time becomes a solid foundation for every religion in the world.